Smarter metrics in climate change and agriculture: Business guidance for target-setting across productivity, resilience and mitigation - Stephenson, Jim; Jarvis, Andrew; Bonilla Findji, Osana; Anderson-Berens, Dylan; Richards, Meryl B. (World Business Council for Sustainable Development, 2020)
This Smarter Metrics Guide helps your company understand and set targets for Climate Smart Agriculture (CSA), which is defined by the UN Food and Agriculture Organization (FAO) according to three priorities or ‘pillars’: - Pillar 1 - Productivity: sustainably increasing agricultural productivity and incomes - Pillar 2 - Resilience: adapting and building resilience to climate change - Pillar 3 - Mitigation: reducing and/or removing/sequestering greenhouse gas (GHG) emissions to limit global warming to 1.5 – 2 degrees Celsius. To support your company’s work on CSA, this guide has two key objectives: • to provide easy, open access information for companies to set and have the confidence to disclose CSA targets, and • to galvanize action and use of CSA as a key solution for transforming food systems and tackling climate change. The audience for this guide is sustainability and risk professionals working in agri- and food businesses, and finance companies. Working together, these groups can ensure you apply this guide using existing resources.